2014
DOI: 10.1089/cbr.2013.1578
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Modulation of Costimulatory and Coinhibitory T-Cell Signaling Molecules on Human Prostate Carcinoma Cells Promotes Productive Antitumor Immune Interactions

Abstract: We sought to determine if single-dose external beam radiation therapy (EBRT) could modulate the expression signature of T-cell costimulatory and coinhibitory molecules in human prostate cancer (PCa) cell lines in vitro. We investigated the functional impact of irradiated PCa cells with a modulated costimulatory profile on responder T-cell activity. We used three PCa cell lines (DU145, PC3, and LNCaP) and two epithelial cell lines from noncancerous prostate and lung tissue. After 72 hours of EBRT, surface expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 39 publications
5
48
0
Order By: Relevance
“…In an attempt to find a potential therapeutic window for the addition of immunotherapeutic treatments, we analysed changes in tumour phenotypes at several time points following SABR. Whereas increased expression of immunostimulatory markers, including OX-40 ligand and 41BB ligand, was evident 72 hours after SABR, decreased expression of PD-L1 (programmed cell death 1 ligand 1), an inhibitor of T-cell expansion and function 28 , for example, was detect up to 144 hours after SABR 20 .…”
Section: Preclinical Evidencementioning
confidence: 97%
See 1 more Smart Citation
“…In an attempt to find a potential therapeutic window for the addition of immunotherapeutic treatments, we analysed changes in tumour phenotypes at several time points following SABR. Whereas increased expression of immunostimulatory markers, including OX-40 ligand and 41BB ligand, was evident 72 hours after SABR, decreased expression of PD-L1 (programmed cell death 1 ligand 1), an inhibitor of T-cell expansion and function 28 , for example, was detect up to 144 hours after SABR 20 .…”
Section: Preclinical Evidencementioning
confidence: 97%
“…SABR involves treatment of tumours with radiation doses that often exceed 5 Gy per fraction with an exceedingly high level of conformality and sharp dose fall-off to spare the surrounding organs at risk. Investigators in many previous studies have focused on the effects of conventional fractionation regimens on the immune system; however, preliminary data suggest that radiation-induced immune responses might be dose-dependent 20,21 . In fact, using radiation doses in the ‘ablative’ range can not only effectively destroy tumour cells directly, but might also encourage these SABR-killed cells to function as a vaccine in situ 22,23 .…”
mentioning
confidence: 99%
“…Animal studies conducted by Huang et al 26 and Filatenkov et al 27 indicated that radiotherapy damages the immunosuppressive tumor microenvironment and subsequently leads to the recruitment of immune cells such as antigen -presenting cells, T cells, and NK cells, which are crucial in antitumor reactions. 28 Bernstein et al 29 have shown that a single dose of 5 Gy, 10 Gy, or 15 Gy increases the expression of costimulatory molecules and Dosimetric parameters of healthy tissues and selected immune factors The exposure of healthy tissue to X -rays was small (TABLE 1). None of the variables: the SABR schedule, dosimetric parameters such as lung volume exposed to ≥20 Gy (V20 Gy, 20-Gy isodose volume of the lungs), mean lung dose (MLD), esophagus mean dose, as well as other radiotherapy parameters correlated with the immune system parameters, serum CRP levels, or WBC count and ANC.…”
Section: (+) and Cd8(+) Lymphocyte Countmentioning
confidence: 99%
“…135 The modulation by radiation of immune checkpoints, namely co-stimulatory and inhibitory molecules on T cells, is under current intensive examination to pave the way for multimodal treatments consisting of radiochemotherapy plus immune therapy. 240,241 The immunological effects of RT are mostly described in patients with melanoma. 242 Non-redundant immune mechanisms get activated in cancer by combining RT with checkpoint inhibitors.…”
Section: Review Toxicology Researchmentioning
confidence: 99%